Association between dietary intake of anthocyanidins and heart failure among American adults: NHANES (2007–2010 and 2017–2018) - Tao, Zaixiao; Zhang, Rui; Zuo, Wenjie; Ji, Zhenjun; Fan, Zhongguo; Chen, Xi; Huang, Rong; Li, Xinxin; Ma, Genshan (Frontiers in Nutrition, 2023)
Background: Despite anthocyanidins have anti-inflammatory and antioxidant properties, no studies have researched association between dietary anthocyanidins and heart failure. Methods: We enrolled 15869 participants from the National Health and Nutrition Examination Survey (NHANES) (2007-2010 and 2017-2018) in this cross-sectional study. We examined baseline data and prevalence of heart failure in different quartile groups of anthocyanin intake (Q1-4). Three models were established through logistic regression to evaluate the protective effect of Q4 (highest anthocyanidins intake) on heart failure. The protective effect of high anthocyanidins intake on heart failure was further evaluated in different subgroups. Results: Participants with the highest anthocyanidins intake (Q4) had the lowest prevalence of heart failure (Q1:2.54%, Q2:2.33%, Q3:2.43%, Q4:1.57%, P = 0.02). After adjusting for possible confounding factors, compared with the Q1 group, the highest anthocyanidins intake (Q4) was independently related to lower risk of heart failure (Q4: OR 0.469, 95%CI [0.289,0.732], P = 0.003). And this association was still stable in subgroups of female, >=45 years, smoker, non-Hispanic White or without diabetes, stroke and renal failure. Conclusion: Dietary intake of anthocyanidins had negative association with the presence of heart failure.